Modified diaphragm for electrolyzed water as well as preparation method and application of modified diaphragm

By adding acidic compounds to the electrolytic separator slurry to modify the zirconia nanoparticles, the problems of poor hydrophilicity and high surface resistance of traditional separator materials are solved, efficient modification of the separator is achieved, and the efficiency of electrolytic hydrogen production is improved.

CN119877031APending Publication Date: 2025-04-25TSINGHUA UNIVERSITY
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411812173.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

Traditional separator materials such as PPS limit the efficiency of hydrogen production by electrolyzing water due to poor hydrophilicity and high surface resistance during the electrolyzing water hydrogen production process.

Method used

The surface of the nanozirconia particles is modified by adding a specific amount of acidic compound to the separator slurry containing zirconia nanoparticles. The modified separator slurry includes polysulfone, zirconia nanoparticles and organic solvents, and the amount of acidic compound is 0.1-10% of the total mass of the separator slurry.

Benefits of technology

The surface resistance of the diaphragm is significantly reduced, the hydrophilicity and ionic conductivity are improved, thereby improving the overall efficiency of hydrogen production by electrolyzing water.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119877031A_ABST
    Figure CN119877031A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of hydrogen production through water electrolysis, in particular to a modified diaphragm for water electrolysis and a preparation method and application of the modified diaphragm. The modified diaphragm for electrolyzed water is prepared from modified diaphragm slurry; the modified diaphragm slurry comprises diaphragm slurry and an acidic compound; the diaphragm slurry comprises polysulfone, zirconium oxide nanoparticles and an organic solvent; the acidic compound comprises one or more of organic acid or inorganic acid. The dosage of the acidic compound is 0.1-10% of the total mass of the diaphragm slurry. According to the modified diaphragm for electrolyzing water, the acidic compound is added into the diaphragm slurry containing the zirconium oxide nanoparticles, the surfaces of the zirconium oxide nanoparticles are modified, the diaphragm is modified, the sheet resistance of the diaphragm is greatly reduced, the ion conduction performance of the diaphragm is remarkably improved, the hydrophilicity of the diaphragm is improved by adding the acidic compound, and the service life of the diaphragm is prolonged. The contact angle is obviously reduced, the wetting ability and the ion conduction efficiency of the electrolyte are enhanced, and the overall efficiency of hydrogen production through water electrolysis can be further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of hydrogen production by water electrolysis, and in particular to a modified diaphragm for water electrolysis and a preparation method and application thereof. Background Art

[0002] In the process of hydrogen production by water electrolysis, the diaphragm is a key component of the electrolyzer, which plays a role in blocking the mixing of anode and cathode gases while allowing effective conduction of electrolyte ions. However, traditional diaphragm materials such as PPS limit the efficiency of hydrogen production by water electrolysis due to their poor hydrophilicity and high surface resistance. Most existing research focuses on improving the conductivity and hydrophilicity of the diaphragm by adding hydrophilic inorganic nano-oxide particles. Although these methods have improved the surface resistance of the diaphragm to a certain extent (0.3 Ω cm²), in the face of the increasingly efficient water electrolysis process, the resistance of the diaphragm still has room to be further reduced.

[0003] Therefore, developing a method that can simply and effectively reduce the surface resistance of the diaphragm is of great significance for improving the efficiency of hydrogen production by water electrolysis. Summary of the invention

[0004] The present invention provides a modified diaphragm for water electrolysis and a preparation method and application thereof, so as to solve the above problems existing in the prior art.

[0005] According to a first aspect of the present invention, the present invention provides a modified diaphragm for water electrolysis, which is prepared from a modified diaphragm slurry; the modified diaphragm slurry comprises a diaphragm slurry and an acidic compound; the diaphragm slurry comprises polysulfone, zirconium oxide nanoparticles and an organic solvent; the acidic compound comprises one or more of an organic acid or an inorganic acid. The amount of the acidic compound is 0.1-10% of the total mass of the diaphragm slurry.

[0006] Optionally, the amount of the acidic compound is 0.1%, 0.5%, 0.8%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10% of the total mass of the diaphragm slurry, and of course it can also be other values ​​within the above range, which is not limited here.

[0007] The present invention modifies the surface of the nano zirconium oxide particles by adding a specific amount of an acidic compound to a diaphragm slurry containing zirconium oxide nanoparticles, thereby improving the hydrophilicity and ion conductivity of the diaphragm, thereby effectively reducing the surface resistance of the diaphragm and improving the overall efficiency of hydrogen production by water electrolysis.

[0008] In order to achieve a better modification effect and thus improve the performance of the modified diaphragm, the acidic compound further includes one or more of lactic acid, formic acid, acetic acid, citric acid, propionic acid, butyric acid, valeric acid, oxalic acid, sulfuric acid and phosphoric acid. These acidic compounds are not only easy to obtain raw materials, but also can interact effectively with the surface of zirconium oxide nanoparticles due to the characteristics of their molecular structure. Among them, carboxyl-containing organic acids (such as lactic acid, formic acid, acetic acid, etc.) form coordination bonds with hydroxyl groups on the surface of zirconium oxide through carboxyl groups; while inorganic acids such as sulfuric acid and phosphoric acid form stable chemical bonds with the surface of zirconium oxide through protonation and multi-dentate coordination ability. This surface modification improves the dispersibility and stability of zirconium oxide nanoparticles.

[0009] Furthermore, the acidic compound is one or more of lactic acid, acetic acid, sulfuric acid and phosphoric acid.

[0010] Preferably, the amount of the acidic compound is 1%-7% of the total mass of the diaphragm slurry, preferably 3%-5%. By limiting the amount of the acidic compound to a reasonable range, the modification effect can be better and the performance of the modified diaphragm can be improved. If the amount of the acidic compound is too low, the contact angle of the obtained diaphragm is too large, the effect of improving the hydrophilicity of the diaphragm is not obvious, and the effect of reducing the surface resistance is not obvious. If the amount of the acidic compound is too high, the mechanical strength and stability of the diaphragm will decrease, and the phase transformation process of the polysulfone will increase the surface resistance.

[0011] Furthermore, the particle size of the zirconium oxide nanoparticles is 50-150 nm. The particle size of the zirconium oxide nanoparticles will affect the porosity, pore size, ion permeability and mechanical strength of the subsequent diaphragm. The present invention has found that it is better to control the particle size within the range of 50-150 nm. In some specific embodiments, the particle size of the zirconium oxide nanoparticles is 100 nm.

[0012] Furthermore, in the diaphragm slurry, the weight ratio of the polysulfone to the zirconium oxide nanoparticles is 2:8-6:4. The polysulfone in the diaphragm slurry has good mechanical strength, excellent acid and alkali resistance and heat resistance, but strong hydrophobicity, and the zirconium oxide nanoparticles are hydrophilic. The hydrophilicity of the diaphragm can be improved by adding zirconium oxide nanoparticles. By limiting the weight ratio of polysulfone to zirconium oxide nanoparticles within a reasonable range, the hydrophilicity of the diaphragm can be better improved.

[0013] Further, the amount of the organic solvent is 50%-70% of the total mass of the diaphragm slurry; and / or, the organic solvent is selected from one or more of NMP, DMF, DMAc and DMSO, preferably NMP. The organic solvent in the diaphragm slurry plays the role of dissolving other components and adjusting the viscosity. By controlling the amount of the organic solvent within a reasonable range and selecting a suitable type of organic solvent, the viscosity and fluidity of the slurry can be better improved, so that other components can be evenly dispersed to form a more stable diaphragm slurry.

[0014] Preferably, the organic solvent is NMP; the acidic compound includes a first acidic compound and a second acidic compound, and the mass ratio of the first acidic compound to the second acidic compound is (1-3): (1-3), preferably (1-3): 1, and more preferably (1-2): 1. The amount of the acidic compound is 3%-5% of the total mass of the diaphragm slurry.

[0015] Further, the first acidic compound is an inorganic acid, and the second acidic compound is an organic acid. Through the synergistic effect of the organic acid and the inorganic acid, the surface resistance and contact angle of the modified diaphragm can be more significantly reduced. In some specific embodiments, the first acidic compound is phosphoric acid, and the second acidic compound is acetic acid.

[0016] According to the second aspect of the present invention, the present invention also provides a method for preparing the above-mentioned modified diaphragm for electrolysis of water, comprising the following steps: mixing polysulfone, zirconium oxide nanoparticles and an organic solvent to prepare a diaphragm slurry; adding an acidic compound to the diaphragm slurry; casting the diaphragm slurry with the acidic compound, and obtaining a modified diaphragm for electrolysis of water after solidification, washing with water and drying.

[0017] The preparation method of the modified diaphragm for electrolysis of water of the present invention uses a tape casting method to form a membrane structure with high production efficiency, stable product quality, and controllable thickness, and then performs a solidification treatment to improve the structural stability of the diaphragm. The diaphragm is washed with water to remove excess acidic substances, and then dried to obtain a diaphragm with a significant modification effect. The preparation method of the present invention is simple and easy to implement, easy to achieve large-scale production, low cost, reduced manufacturing cost, significant modification effect, and improved efficiency of hydrogen production by electrolysis of water, and can be widely used in the field of hydrogen production by electrolysis of water.

[0018] Furthermore, the preparation method includes the following steps: mixing polysulfone, zirconium oxide nanoparticles and an organic solvent, stirring evenly (rotation speed 500-800rpm, temperature 20-30℃, time 2-4h), standing to remove bubbles (time 0.5-1h), and preparing a diaphragm slurry; adding an acidic compound to the diaphragm slurry, and continuing to stir evenly (rotation speed 300-500rpm, time 0.5-1.5h); using an automatic coating machine to cast the diaphragm slurry after adding the acidic compound (scraper height 400-600μm, speed 2-4cm / s), then immersing the cast film in 20-30℃ deionized water for coagulation (time 0.5-1.5h), and then repeatedly rinsing with deionized water 2-3 times to remove residual solvents and acidic substances, and finally hot air drying at 50-70℃ for 3-5h to obtain a modified diaphragm for electrolysis of water.

[0019] According to a third aspect of the present invention, the present invention further provides a water electrolysis hydrogen production device, comprising the above-mentioned modified diaphragm for water electrolysis.

[0020] The electrolysis water hydrogen production device generally includes an electrolytic cell, an electrode and a diaphragm. When powered on, hydrogen is produced on the cathode side and oxygen is produced on the anode side. The electrolysis water hydrogen production device of the present invention adopts the modified diaphragm for electrolysis water with both low surface resistance and low contact angle, thereby improving the electrolysis efficiency of the alkaline water electrolysis device.

[0021] Beneficial effects of the present invention: The modified diaphragm for water electrolysis provided by the present invention modifies the surface of the nano zirconium oxide particles by adding an acidic compound to the diaphragm slurry containing zirconium oxide nanoparticles, thereby modifying the diaphragm, greatly reducing the surface resistance of the diaphragm, and significantly improving its electrical conductivity. By adding the acidic compound, the hydrophilicity of the diaphragm is improved, the contact angle is significantly reduced, the wetting ability of the electrolyte and the ion conduction efficiency are enhanced, and the overall efficiency of hydrogen production by water electrolysis can be improved. Compared with the prior art, the present invention only needs to add an acidic compound to the diaphragm slurry, does not require a complex surface treatment process, and is suitable for industrial large-scale production. Acidic substances are diverse, easy to obtain, and added in small amounts, which has little impact on production costs. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0023] Figure 1 A flow chart for preparing a modified diaphragm for water electrolysis provided in an embodiment of the present invention.

[0024] Figure 2 This is an electron microscope image of the surface and cross-section of a modified diaphragm for water electrolysis according to an embodiment of the present invention.

[0025] Figure 3 This is a physical picture of a modified diaphragm for water electrolysis according to an embodiment of the present invention.

[0026] Figure 4 The figure is a comparison diagram of the contact angles of the modified diaphragms for water electrolysis prepared by using different acidic compounds in the present invention. DETAILED DESCRIPTION

[0027] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with the drawings of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] Examples 1-4 The present embodiment provides a modified diaphragm for electrolysis of water, which is prepared from a modified diaphragm slurry; the modified diaphragm slurry includes a diaphragm slurry and an acidic compound; the diaphragm slurry is composed of polysulfone (molecular weight of 20,000-80,000), zirconium oxide nanoparticles (particle size of 100 nm) and NMP in a weight ratio of 5:7:12; the acidic compound is shown in Table 1 below, and the amount of the acidic compound is 3% of the total mass of the diaphragm slurry.

[0029] Preparation method of modified diaphragm for water electrolysis Figure 1 As shown, the method comprises the following steps: mixing polysulfone, zirconium oxide nanoparticles and an organic solvent, stirring evenly (rotating speed 800 rpm, temperature 25°C, time 4h), standing to remove bubbles (time 1h), and obtaining a diaphragm slurry; adding an acidic compound to the diaphragm slurry, and continuing to stir evenly (rotating speed 500 rpm, time 1h); using an automatic coating machine to cast the diaphragm slurry after adding the acidic compound (scraper height 500 μm, speed 3 cm / s), then immersing the cast film in 25°C deionized water for solidification (time 1h), and then repeatedly rinsing with deionized water 3 times to remove residual solvents and acidic substances, and finally drying with hot air at 60°C for 4h to obtain a modified diaphragm for electrolyzed water.

[0030] The electron microscope images of the surface and cross section of the modified diaphragm for electrolysis of water in Example 4 are as follows: Figure 2As shown, it can be seen that the modified membrane surface porous structure is regularly distributed, the pore size is uniform, and there is no obvious agglomeration and defects; the cross section presents a typical asymmetric finger-like porous structure with abundant interconnected pores. This special structure is conducive to the rapid conduction of electrolyte ions. Figure 3 As shown, it can be seen that the prepared modified diaphragm has a uniform milky white color, a smooth surface, and good flexibility and mechanical properties, which indicates that the addition of acidic compounds does not affect the molding properties of the diaphragm and can meet the needs of practical applications.

[0031] Comparative Example 1 This comparative example provides a diaphragm for water electrolysis, which is different from Example 1 in that no acidic compound is added.

[0032] The membranes of Examples 1-4 and Comparative Example 1 were subjected to surface resistance and contact angle tests, where the surface resistance test was conducted using a four-probe method and the contact angle test was conducted using a contact angle meter. The test results are shown in Table 1 below.

[0033] Table 1

[0034] Comparative experimental contact angles of different acidic compounds Figure 4 As shown in Table 1, the test results show that when phosphoric acid is used as the acidic compound, the modified diaphragm has the lowest surface resistance and the lowest contact angle, indicating that phosphoric acid modification can most effectively improve the hydrophilicity and conductivity of the diaphragm. The lower the contact angle, the better the hydrophilicity of the diaphragm, which is conducive to the wetting of the electrolyte and the rapid conduction of ions, thereby improving the electrolysis efficiency.

[0035] Embodiment 5-8 This embodiment provides a modified diaphragm for water electrolysis, which is different from Embodiment 4 in that the amount of phosphoric acid added is different, and the specific differences are shown in Table 2 below.

[0036] Table 2

[0037] The results in Table 2 show that when the phosphoric acid addition amount is 3%-5%, the surface resistance of the modified diaphragm is the lowest and the contact angle is significantly reduced. When the addition amount exceeds 5%, the surface resistance shows an upward trend. Therefore, the optimal phosphoric acid addition amount is 3%-5%.

[0038] Examples 9-13 This embodiment provides a modified diaphragm for electrolyzing water, which is different from Embodiment 4 in that the acidic compound includes phosphoric acid and acetic acid, and the amount of the acidic compound added is 3%, wherein the amount of phosphoric acid added and the amount of acetic acid added are shown in Table 3 below.

[0039] Table 3

[0040] The results in Table 3 show that when phosphoric acid and acetic acid are compounded in a mass ratio of 1.5:1.5 (Example 9), the modified diaphragm exhibits the best overall performance: the surface resistance is reduced to 0.09 Ω cm², which is significantly lower than the case of using phosphoric acid (0.11 Ω cm²) or acetic acid (0.12 Ω cm²) alone. This significant performance improvement indicates that the two acids have a significant synergistic effect near the equal mass ratio. As the ratio deviates from 1:1, although the modification effect is still better than the use of a single acid, the performance gradually decreases. This synergistic effect may be due to the fact that the acidic groups of two different structures can modify the surface of the zirconium oxide nanoparticles more evenly and stably, forming a more effective modified structure.

[0041] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A modified diaphragm for water electrolysis, characterized in that: Prepared from modified diaphragm slurry; the modified diaphragm slurry includes diaphragm slurry and acidic compound; the diaphragm slurry includes polysulfone, zirconium oxide nanoparticles and organic solvent; The acidic compound includes one or more of an organic acid or an inorganic acid; the amount of the acidic compound used is 0.1-10% of the total mass of the diaphragm slurry.

2. The modified diaphragm for water electrolysis according to claim 1, characterized in that: The acidic compound is selected from one or more of lactic acid, formic acid, acetic acid, citric acid, propionic acid, butyric acid, valeric acid, oxalic acid, sulfuric acid and phosphoric acid.

3. The modified diaphragm for water electrolysis according to claim 2, characterized in that: The acidic compound is selected from one or more of lactic acid, acetic acid, sulfuric acid and phosphoric acid.

4. The modified diaphragm for water electrolysis according to claim 1, characterized in that: The amount of the acidic compound used is 1%-7% of the total mass of the diaphragm slurry, preferably 3%-5%.

5. The modified diaphragm for water electrolysis according to claim 1, characterized in that: In the diaphragm slurry, the weight ratio of the polysulfone to the zirconium oxide nanoparticles is 2:8-6:

4.

6. The modified diaphragm for water electrolysis according to any one of claims 1 to 5, characterized in that: The particle size of the zirconium oxide nanoparticles is 50-150 nm.

7. The modified diaphragm for water electrolysis according to claim 1, characterized in that: The amount of the organic solvent used is 50%-70% of the total mass of the diaphragm slurry; and / or, the organic solvent is selected from one or more of NMP, DMF, DMAc and DMSO, preferably NMP.

8. The modified diaphragm for water electrolysis according to claim 1, characterized in that: The organic solvent is NMP; the acidic compound includes a first acidic compound and a second acidic compound, and the mass ratio of the first acidic compound to the second acidic compound is (1-3): (1-3); The amount of the acidic compound used is 3%-5% of the total mass of the diaphragm slurry.

9. The method for preparing a modified diaphragm for water electrolysis according to any one of claims 1 to 8, characterized in that: The method comprises the following steps: mixing polysulfone, zirconium oxide nanoparticles and organic solvent to prepare diaphragm slurry; adding acidic compounds into the diaphragm slurry; casting the diaphragm slurry with acidic compounds, solidifying, washing and drying to obtain a modified diaphragm for water electrolysis.

10. A hydrogen production device by electrolysis of water, characterized in that: The modified diaphragm for water electrolysis comprises the modified diaphragm for water electrolysis according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Preparation method of modified nano-composite diaphragm for high-hydrophilicity alkaline electrolyzed water

    CN117431586A

  • Preparation method of polysulfone / inorganic composite diaphragm for alkaline electrolyzed water

    CN117702183A

  • Alkaline electrolytic water hydrogen production diaphragm and preparation method thereof

    CN117779104A

  • Alkaline water electrolysis composite diaphragm as well as preparation method and application thereof

    CN118186492A

  • Proton acid doped high-performance PEM water electrolyte proton exchange membrane

    CN118422272A